Zaytinya : delicious Mediterranean dishes from Greece, Turkey, and Lebanon - Andrés, José, 1969-; Costa, Michael (Cookbook author) (Ecco, an imprint of HarperCollins Publishers, 2024)
"Since Chef José Andrés opened the doors to his restaurant Zaytinya twenty years ago, food lovers have savored his creative adaptations of the classic dishes of Greece, Turkey, and Lebanon. Zaytinya's menu has always showcased the region's extraordinary food traditions while innovating in José's signature style: delicious, surprising, and made for sharing. From crispy fried vegetables and perfectly spiced seafood to tender grilled kebabs and warm, fluffy pita, these recipes are simply irresistible as well as accessible to the home cook. The smooth dips and delectable roasts will happily feed a family on a weeknight or friends over for weekend dinner. Zaytinya--which draws its name from the Turkish word for olive oil--brings to life the ingredients, techniques, dishes, and histories that are central to the way many of us love to eat today"--